KONSEP DAN TUJUAN PENDIDIKAN SEKS PADA ANAK JENJANG SEKOLAH DASAR BERBASIS AL-QUR’AN - Budianto (Tashfiyatuna: Jurnal Pendidikan Keislaman, 2026)
Sex education for primary school children is increasingly urgent amid digital exposure and risks of social deviance, yet its implementation remains constrained by stigma and the lack of a systematic Islamic framework. This study aims to reconstruct the concept and formulate the objectives of Qur'an-based sex education using a qualitative literature approach with the maudhu'i tafsir method and content analysis. The findings reveal three main pillars: internalization of ḥayā’, privacy management through isti’dzan, and self-control. Based on these, five objectives are formulated: moral identity formation, respect for privacy, self-control, bodily protection, and prevention of deviant behavior. Effective implementation requires synergy among families, schools, and communities. Qur'an-based sex education serves as a strategy to build protective character and preserve children's morality from an early age.